Exact statistical inference for categorical data - Shan, Guogen (Elsevier, 2016)
Exact Statistical Inference for Categorical Data discusses the way asymptotic approaches have been often used in practice to make statistical inference. This book introduces both conditional and unconditional exact approaches for the data in 2 by 2, or 2 by k contingency tables, and is an ideal reference for users who are interested in having the convenience of applying asymptotic approaches, with less computational time. In addition to the existing conditional exact inference, some efficient, unconditional exact approaches could be used in data analysis to improve the performance of the testing procedure. Demonstrates how exact inference can be used to analyze data in 2 by 2 tables Discusses the analysis of data in 2 by k tables using exact inference Explains how exact inference can be used in genetics.